Digital Twins in IT: Enhancing System Monitoring and Predictive Maintenance - Kambala, Gireesh (International Journal of Scientific Research and Management (IJSRM), 2023)
Digital twin technology is transforming IT infrastructure management by enabling real-time system monitoring and predictive maintenance. A digital twin is a virtual representation of a physical IT system that continuously updates based on real-time data, allowing for enhanced visibility, performance analysis, and failure prediction. With the integration of Artificial Intelligence (AI), Machine Learning (ML), Internet of Things (IoT) sensors, and cloud computing, digital twins are redefining how IT systems are managed, minimizing downtime and optimizing resource utilization.This paper explores the architecture, applications, and benefits of digital twins in IT, focusing on their role in proactive maintenance and system optimization. It highlights how real-time monitoring through digital twins enables early detection of system anomalies, predictive analytics for failure prevention, and cost-effective maintenance strategies. The study presents comparative insights between traditional IT monitoring approaches and AI-powered digital twin solutions, demonstrating the superior efficiency and accuracy of the latter.Furthermore, the paper discusses the challenges associated with digital twin implementation, including high initial costs, data security concerns, and integration complexities. Emerging trends such as self-learning AI models, blockchain-enhanced security, and the increasing adoption of digital twins in cloud computing are also examined. The research is supported by tables and graphs illustrating cost savings, efficiency improvements, and market growth projections in digital twin applications.The findings suggest that digital twins will play a critical role in IT infrastructure management, offering enterprises a scalable and intelligent approach to optimizing their systems. Despite existing barriers, ongoing advancements in AI, data analytics, and cybersecurity are expected to drive wider adoption and greater operational benefits in the coming years.